Investment policy, internal financing and ownership concentration in the UK - Goergen, Marc; Renneboog, Luc (Journal of Corporate Finance, 2001)
This paper investigates whether investment spending of firms is sensitive to the availability of internal funds. Imperfect capital markets create a hierarchy for the different sources of funds such that investment and financial decisions are not independent. The relation between corporate investment and free cash flow is investigated using the Bond and Meghir [Review of Economic Studies, 61 (1994a) 197] Euler-equation model for a panel of 240 companies listed on the London Stock Exchange over a 6-year period. This method allows for a direct test of the first-order condition of an intertemporal maximisation problem. It does not require the use of Tobin's q, which is subject to mismeasurement problems. Apart from past investment levels and generated cash flow, the model also includes a leverage factor which captures potential bankruptcy costs and the tax advantages of debt. More importantly, we investigate whether ownership concentration by class of shareholder creates or mitigates liquidity constraints. When industrial companies control large shareholdings, there is evidence of increased overinvestment. This relation is strong when the relative voting power (measured by the Shapley values) of the combined equity stakes of families and industrial companies and the Herfindahl index of industrial ownership are high. This suggests that a small coalition of industrial companies is able to influence investment spending. In contrast, large institutional holdings reduce the positive link between investment spending and cash flow relation and, hence, suboptimal investing. Whereas there is no evidence of over- or underinvesting at low levels of insider shareholding, a high concentration of control in the hands of executive directors reduces the underinvestment problem.